Seeing Is Believing: Making Wellbeing More Tangible - Vella-Brodrick, Dianne A.; Gill, Anneliese; Patrick, Kent (Frontiers in Psychology, 2022)
Positive Psychology has been instrumental in promoting wellbeing science in the modern era. However, there are still ways in which positive psychology interventions and positive education programs can be improved to achieve more robust and sustained effects. One suggested method is to make wellbeing more salient and tangible, particularly through the use of objective tools that assess the relationship between psychological and physiological wellbeing and enable wellbeing progress to be seen. Add an interdisciplinary team, as well as technology-enabled and pedagogically sound learning tools and approaches, and the potential for positive outcomes and impact increases exponentially. Observing and tracking wellbeing progress in this way can provide evidence, motivation and belief in positive psychology and wellbeing interventions that can lead to engaged learning, sustained benefits and systemic impact. Positive psychology needs to strategically extend on the emerging work in this field to help everyone, including policy makers, notice and value wellbeing.